Exploring the antecedents of capability, motivation and opportunity in HR analytic competency - Gayathri, R; Dr. Asha Nadig (International Journal of Advanced Science and Technology, 2020)
Research Background: Human Resource analytics (HRA) commonly known as talent/workforce/people analytics is a data-driven discipline in Human Resource Management (HRM). In this domain HR analysts with various competencies such as analytical skill, business acumen, etc. are responsible for collecting and processing of data to enable the cost effective decision-making process. The capability, motivation and opportunity-enhancing HRM practices have given positive directions to various organizational outcomes. This article attempts to explore the antecedents of capability, opportunity and motivation components required for the competency of HR analysts. Methodology: In this study, the framed hypothesis tests the influence of capability, opportunity and motivation in HR analytic competency. A well-structured questionnaire was used to collect the data from 230 HR analytics professionals working in different organization within the limits of Bangalore city, India. The mean score, MANOVA analysis and Friedman rank test were performed to statistically analyze the data. Major findings and conclusion: A positive and significant relation was found between the capability, opportunity and motivation, and HR analytic competency. Our study suggests that antecedents of HR capability (behaviour), motivation (job satisfaction) and opportunity (cross-functional dynamics) affects the HR analytics competency in terms of understanding of data and both analytical and interpretation skill. Our study emphasizes on establishment of the capability, opportunity and motivation-based HR practices to improve the competency of HR professionals.